The Great Wall of China - Noll, Elizabeth (Seven wonders of the modern world (Bellwether Media), 2021)
Presents the history, construction, maintenance, and popularity of the Great Wall of China. Includes color photographs, fact boxes, a timeline, a glossary, and additional resources.